KEEFEKTIFAN METODE PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR DAN MOTIVASI SISWA PADA PELAJARAN MATEMATIKA KELAS V SD N 02 TUMBAL PEMALANG - Fajar Cahyadi, Izza Ni?óÔé¼Ôäóamah (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2013)
The problems discussed in this study is "whether there is the effectiveness of inquiry learning methods on learning outcomes and motivation of students in math class V Tumbal elementary school 02".?é?áThe data in this study were obtained by using the method of documentation, tests, interviews, and questionnaires.?é?áThis study is an experimental study with a quantitative approach.?é?áThe design of this research study Exsperimental True Design.?é?á(Experiment truly) in the form of Posttest-Only Control Design.?é?áBy using a sampling technique that is saturated sampling.?é?áResults mastery learning classical analysis by t test of the experimental group obtained t> t table (8.553> 1.676), in the control group known t <t table (1.664 <1.676).?é?áSo learning by inquiry method can achieve mastery class.?é?áTo determine differences in student learning outcomes using the t test, known t> t table (2.030> 2.012) then Ho is rejected, it means that the learning outcomes of the experimental group over the control group so that there are differences in learning outcomes experimental group with the control group.?é?áCalculation of the experimental group students' motivation questionnaire contained 68% of students have excellent category, in the control group there were 44% of students have excellent category.?é?áSo the motivation to study the experimental group was better than control group.?é?áIt can be concluded that the method of inquiry learning can effectively improve learning outcomes and motivation fifth grade elementary school students 02 Tumbal.Top of Form?é?á